Immune responses to the hepatitis B surface antigen and liver-specific lipoprotein in acute type B hepatitis. Issue 3 (March 1977) - Lee, W M; Reed, W D; Osman, C G; Vahrman, J; Zuckerman, A J; Eddleston, A L; Williams, R
Abstract : A serial prospective study of cellular immunity to HBsAg and liver-specific membrane lipoprotein was undertaken in 21 adults with acute hepatitis type B. Cellular immunity to HBsAg as determined by leucocyte migration inhibition with partially purified HBsAg as antigen was detected in all the patients during the recovery phase of the illness and was already detectable at the time of admission in 13 (62%) of the cases. In five of the remaining eight the titre of HBsAg in the serum at this time was high and in the whole series there was an inverse correlation between the degree of migration inhibition on admission and the peak HBsAg titre suggesting that antigen or possibly antigen/antibody complexes might be interfering with the demonstration of cellular immunity in vitro. Using a combination of minimum migration index recorded during the recovery period peak HBsAg titre, it was possible to compute the peak aspartate aminotransferase level with reasonable accuracy, a finding consistent with the hypothesis that the severity of the illness is related to both the number of infected hepatocytes and the vigour of the immune response to HBsAg. Evidence of an immune response to the liver-specific hepatocyte membrane lipoprotein was present in 50% of the patients tested at the time of admission, but was transient, having disappeared in every case by four weeks. The minimum migration index recorded with HBsAg as antigen was significantly lower in those with detectable sensitisation to the lipoprotein and it is possible that this autoimmune reaction is also generated by the interaction of T cells with viral antigenic determinants on the liver cell surface.